Variation in Patients' Hospice Costs - Haiden A. Huskamp; Joseph P. Newhouse; Jessica Cafarella Norcini; Nancy L. Keating (SAGE Publishing, 2008)
We obtained patient-level cost data from one hospice to explore variation in hospice costs across patients. We found that average per day costs decreased as duration of hospice stay increased. Costs per day were lower for nursing home residents than nonresidents. We identify possible alterations to the Medicare per diem payment system that could address these issues, including higher per diems for the first and last days and an adjuster for nursing home residence. However, replicating these results using data from a broader, more representative sample of hospices is needed before making changes to the per diem system.